Genetic Alterations in Oxidant and Anti-Oxidant Enzymes in the Vascular System - Awad, Maan A.; Aldosari, Sarah R.; Abid, M. Ruhul (Frontiers in Cardiovascular Medicine, 2018)
Cardiovascular diseases (CVD) are one of the prime causes of mortality worldwide. Experimental animal models have become a valuable tool to investigate and further advance our knowledge on etiology, pathophysiology and intervention. They also provide a great opportunity to understand the contribution of different genes and effector molecules in the pathogenesis and development of diseases at the sub-cellular levels. High levels of reactive oxygen species (ROS) have been associated with the progression of CVD such as ischemic heart disease (IHD), myocardial infarction, hypertension, atherosclerosis, aortic aneurysm, aortic dissection and others. On the contrary, low levels of antioxidants were associated with exacerbated cardiovascular event. Major focus of this review is on vascular pathogenesis that leads to CVD, with special emphasis on the roles of oxidant/antioxidant enzymes in health and disease progression in vascular cells including vascular endothelium. The major oxidant enzymes that have been implicated with the progression of CVD include NADPH Oxidase, nitric oxide synthase, monoamine oxidase, and xanthine oxidoreductase. The major antioxidant enzymes that have been attributed to normalizing the levels of oxidative stress include superoxide dismutases, catalase and glutathione peroxidases, and thioredoxin. Cardiovascular phenotypes of major oxidants and antioxidants knockout and transgenic animal models are discussed here.